Business analysis and valuation : - Palepu, Krishna G. (South-Western, 1995)
This book differs from other textx in business and financial analysis in a number of important ways. In the first two parts, the book introduces and develops a framework for business analysis and valuation using financial statement data. In part 3, it shows how this framwork can be applied to a variety of decision contexts. Part 4 provides a variety of cases that can be used to develop the concepts discussed in the text. The book use Compaq Computer Corporation, whose annual report data are provided in part 5